2012
DOI: 10.1210/me.2011-1283
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchidism in Mice with an Androgen Receptor Ablation in Gubernaculum Testis

Abstract: Androgens play a critical role in the development of the male reproductive system, including the positioning of the gonads. It is not clear, however, which developmental processes are influenced by androgens and what are the target tissues and cells mediating androgen signaling during testicular descent. Using a Cre-loxP approach, we have produced male mice (GU-ARKO) with conditional inactivation of the androgen receptor (Ar) gene in the gubernacular ligament connecting the epididymis to the caudal abdominal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 32 publications
7
82
0
4
Order By: Relevance
“…Testicular descent GU-ARKO Rarb-Cre Gubernacular ligament Cryptorchidism, smaller testes and epididymides, early subfertility, and late infertility [88]. SM-ARKO SM22a-Cre Smooth muscle cells No effect on testicular descent [88].…”
Section: Ptm-arko Smmhc-crementioning
confidence: 99%
See 1 more Smart Citation
“…Testicular descent GU-ARKO Rarb-Cre Gubernacular ligament Cryptorchidism, smaller testes and epididymides, early subfertility, and late infertility [88]. SM-ARKO SM22a-Cre Smooth muscle cells No effect on testicular descent [88].…”
Section: Ptm-arko Smmhc-crementioning
confidence: 99%
“…SM-ARKO SM22a-Cre Smooth muscle cells No effect on testicular descent [88]. M-ARKO ACTA1-Cre Skeletal muscles No effect on testicular descent [88].…”
Section: Ptm-arko Smmhc-crementioning
confidence: 99%
“…Jensen MS et al concluded that smoking more than 10 cigarettes a day during pregnancy increased the risk of cryptorchidism. Jensen MS et al [2] & Kaftanovskaya EM et al [3] concluded that the second inguino-scrotal stage of testicular descent is clearly androgen-dependent [3]. The diagnosis of cryptorchidism is made by physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…(Jensen et al, 2007) Kaftanovskaya EM et al concluded that the second inguino-scrotal stage of testicular descent is clearly androgen-dependent. (Kaftanovskaya et al, 2012) The diagnosis of cryptorchidism is made by physical examination. The diagnosis of cryptorchidism should be considered when non-palpable testis and inguinal hernia are present, although, each patient might experience the symptoms differently.…”
Section: Discussionmentioning
confidence: 99%